Duplicate Land Certificates and Good Faith Buyers: Legal Vulnerability and Judicial Protection in Indonesian Property Law - Karmila Karmila (Journal of Law, Social Science and Management, 2026)
Introduction: Duplicate land certificates represent a critical source of legal uncertainty in Indonesia's agrarian system. Administrative negligence and weak verification procedures by the National Land Agency (BPN) have enabled overlapping certificate issuance, placing good faith buyers in a position of structural vulnerability where formally valid titles may still be annulled. Objectives: This study examines the legal position of good faith buyers confronted with duplicate certificates, the allocation of responsibility between BPN and private parties, and patterns of judicial reasoning in resolving such disputes. Method: A normative juridical method was employed, combining statutory analysis of the UUPA, Government Regulation No. 24/1997, and Supreme Court Circular Letters (SEMA) No. 7/2012 and No. 4/2016, with qualitative content analysis of selected judicial decisions and a conceptual framework of preventive versus repressive legal protection. Results: Four protection categories were identified—preventive, repressive, administrative, and digital—each operating with significant doctrinal inconsistencies. Courts inconsistently applied good faith standards, BPN liability was rarely enforced, and electronic certificates addressed forgery risks without resolving existing overlaps. Conclusion: Effective protection for good faith buyers requires substantive legislative reform, including binding codification of good faith doctrine, a dedicated state compensation mechanism for registration errors, and systematic registry data cleansing beyond current e-certificate initiatives.